The Doctrin to Educate Children without Violence in Islam - Muafiah, Evi (Association of Indonesian Islamic Kindergarten Teachers Education Study Program, 2016)
Islam was revealed to the Prophet Muhammad as rahmatan li al-alamin of which teaches us to always love and cherish all of Gods creatures, both animate and inanimate creatures. Children is Godâs mandate that accompanies the affection between mother and father, so they can ensure to give their children a nurturing full with love and positive affection. The atmosphere of nurturing is certainly not to be interfered with both verbal and physical violence, because these two things are very contradictory. Islam teaches us how to educate children without violence. Violence should only be done as a last resort and that too done to foster not hurt. Prophet Muhammad SAW is a role model how to educate children properly. Even when he is praying, he patiently allowing the children to ride his back when he was on prostration. Keywords: children in the perspective of the holy Koran, the characteristics and needs of children, child learning methods. Islam diturunkan kepada Rasulullah Muhammad Saw sebagai rahmatan li al-âalamin, yang di antaranya mengajarkan kita untuk selalu saling mengasihi dan menyayangi sesama makhluk Allah, baik yang hidup maupun benda mati. Anak adalah amanah Allah yang hadir menyertai kasih sayang antara ibu dan bapaknya, maka sudah sewajarnya jika kemudian orang tua mengasuhnya dalam suasan penuh kasih dan sayang. Suasana tersebut tentunya jangan sampai dicampuri dengan kekerasan baik verbal maupun fisik, karena kedua hal tersebut sangat bertentangan. Islam mengajarkan kepada kita bagaimana mendidik anak tanpa kekerasan. Kekerasan hanya boleh dilakukan sebagai alternatif terakhir dan itupun dilakukan untuk membina bukan menyakiti. Rasulullah Saw merupakan contoh bagaimana mendidik anak dengan baik. Bahkan saat shalat pun beliau dengan sabar mengasuh anak-anak dengan membiarkan punggungnya dinaiki anak-anak saat beliau sujud. Kata kunci: anak dalam perspektif al-Qurâan, karakteristik dan kebutuhan anak, metode pembelajaran anak